Empirical Modelling of Norwegian Import Prices - Ida Wolden Bache (Norges Bank, 2002)
In this paper we investigate the formation of Norwegian import prices of manufactures over the period 1970(1)-1998(3), thereby extending the sample period used in the study by Naug and Nymoen (1996). If international goods markets are perfectly integrated and the law of one price holds, then for a small open economy we would expect import prices to be exogenously given in foreign currency and to fully respond to movements in the exchange rate. However, empirical studies of small open economies have shown that exchange rate changes are not fully reflected in import prices, and that domestic variables have significant effects on import prices. Applying both single-equation and multivariate cointegration analysis we find evidence of a long-run cointegrating relationship between Norwegian import prices, foreign export prices measured in domestic currency, domestic unit labour costs, and the domestic unemployment rate. Our results indicate that exchange rate pass-through is complete in the long run. In contrast, Naug and Nymoen (1996) report a long-run pass-through coefficient of 0.63.
hdl:11250/2498660
Keywords: C51; E31; F31; 330; import prices; exchange rate pass-through; equilibrium-correction models